2022
DOI: 10.1371/journal.pone.0274540
|View full text |Cite
|
Sign up to set email alerts
|

Death-coping self-efficacy and its influencing factors among Chinese nurses: A cross-sectional study

Abstract: Background Nurses are the main caregivers of dying patients. Facing or dealing with death-related events is inevitable. Death-coping self-efficacy (DCS) is very important, as it can reduce the risk of nursing staff to adverse emotional distress, help them participate in end-of-life care and improve the quality of care of patients. Methods Using the convenient sampling method, this study included a total of 572 nurses from a tertiary hospital in Hangzhou, China. The status and influencing factors of the DCS o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
1
0
0
1
Order By: Relevance
“…Nurses specialized in palliative care demonstrated a higher capability to cope with death (OR = 1.503), consistent with related research [33]. One plausible explanation is that in China, palliative care specialists are subjected to comprehensive, structured training programs and must clear a stringent certi cation procedure to earn their quali cations.…”
Section: Factors In Uencing Death Coping Abilitysupporting
confidence: 82%
“…Nurses specialized in palliative care demonstrated a higher capability to cope with death (OR = 1.503), consistent with related research [33]. One plausible explanation is that in China, palliative care specialists are subjected to comprehensive, structured training programs and must clear a stringent certi cation procedure to earn their quali cations.…”
Section: Factors In Uencing Death Coping Abilitysupporting
confidence: 82%
“…Since palliative care for children has not yet been widely promoted in clinical practice in mainland China, most clinicians in this research have had little experience in this area. The results ( Table 2 ) may imply that inadequate understanding of pediatric palliative care, inadequate support from colleagues, and lack of clarity about the child’s terminal moment may influence clinicians’ misperceptions of palliative care and lead to strong emotional reactions because most clinicians, patients, and families of dying children may be unprepared to face the death of a child [ 4 , 6 , 13 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…As we know, helping families understand the ineffectiveness of current treatments is an important step in choosing palliative care for critically ill children [ 19 , 20 ]. The literature also revealed that, due to inadequate communication and fear of medical disputes, even if clinicians recognize that ineffective treatment prolongs physical and mental suffering in critically ill children, most tend to repress their own feelings and values, leaving critical medical decisions to the families of patients in hopes of minimizing medical conflicts and disputes [ 4 , 16 , 17 , 18 , 19 ]. This could explain why research participants, particularly physicians and those with more experience in end-of-life care, expressed a need for training in communication skills ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, não foi possível comparar esses resultados à luz da literatura, uma vez que estudos anteriores sobre como os profissionais lidam com a morte utilizaram principalmente indicadores específicos como autoeficácia na morte (24)(25) , atitude em relação à morte (26)(27)(28) ou a origem desses recursos, sejam eles intrínsecos ou extrínsecos (3) . Entre enfermeiros, muitos dos estudos realizados recentemente têm um desenho qualitativo (3,(5)(6) .…”
Section: Discussionunclassified